Employee Creativity Management Capability and Corporate Sustainability: Empirical Evidence from Furniture Exporting Businesses in Thailand - Chinchang, Pattarika; Pratoom, Karun; Jhundra-indra, Prathanporn (วารสารการบัญชีและการจัดการ, 2019)
Employee creativity management capability has been recognized as one of the foremost capabilities which influence on business competitiveness, firm success, and corporate sustainability. The aim of this study was to investigate the relationship among employee creativity management capability’s dimension and, its consequences. Data were derived from a survey of 139 furniture exporting businesses in Thailand. The regression analysis was used to verify the hypotheses. The results highlighted that new ideas generation orientation, working practice originality implementation, and job improvement value focuses had a significant positive effect on business competitiveness. Likewise, job improvement value focus and creative solution usefulness competency had a significant positive effect on firm success. Moreover, the results also showed the relationship among business competitiveness, firm success, and corporate sustainability. Theoretical and managerial contributions, conclusion, and suggestions for future research are also presented.